Globally competent teachers: English as a second language teachers’ perceptions on global competence in English lessons - Yaccob, Nur Syafiqah; Yunus, Melor Md.; Hashim, Harwati (Frontiers in Psychology, 2022)
Due to the implementation of global education and global citizenship education in the 21st century, more focus is given to developing teachers’ global competence in English language teaching. This study aims to examine the perceptions of English as a Second Language (ESL) teachers of (1) global competence integration in English teaching and (2) the professional development programs organized by the Ministry of Education (MOE) for their global competence development. A web-survey questionnaire was distributed to 172 Malaysian ESL teachers based on selected criteria. The data collected were analyzed descriptively. The main findings indicated that most ESL teachers showed positive perceptions regarding the importance of global competence and integration in English lessons. Although 83.1% of the 172 participants agreed to have attended 10 or more programs related to developing global competence, the descriptive analysis found the ESL teachers’ moderate knowledge and understanding of what constitutes global competence. In contrast, a high agreement was found regarding their perceptions of the importance of global competence in ESL lessons. Also, most respondents revealed the lack of support from the MOE through professional development programs specifically structured to develop ESL teachers’ global competence. The findings served as a template for a larger-scale study that focuses on implementing global competence in the local non-western context.